Sphenoid Dysplasia: A Rare Presentation of Infantile Myofibroma. Issue 2 (March 2018) - Kini, Ashwini; Syed, Reema; Compton, Christopher; Hata, Jessica L.; Ramasubramanian, Aparna
Abstract : The authors report a case of isolated congenital orbital myofibroma causing sphenoid dysplasia and presenting as global restriction of extraocular motility and ptosis in a neonate. Sphenoid wing dysplasia is most commonly associated neurofibromatosis 1 but this patient had no evidence of neurofibromatosis on clinical examination and genetic testing. Congenital orbital myofibroma can have secondary effects on bone and likely the lesion was present early in development leading to aplasia of the sphenoid bone. To the best of the authors' knowledge, this is the first reported case of sphenoid wing aplasia secondary to congenital orbital myofibroma independent of neurofibromatosis 1. Abstract : An infiltrating orbital myofibroma during fetal development can cause congenital sphenoid wing aplasia which may present as restrictive childhood strabismus and should prompt early imaging.Supplemental Digital Content is available in the text.